1996
DOI: 10.1021/jp953127x
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR and Quantum Chemical Studies of the Interaction between Dimethyl Ether and HZSM-5 Zeolite

Abstract: Adsorption of dimethyl ether (DME) on the protonated ZSM-5 zeolite was investigated by FT-IR spectroscopy and density functional theory (DFT) calculation. The coverage and temperature dependencies of characteristic bands and the adsorption on the partially deuterated zeolite were studied by FT-IR. Three bands observed at ca. 2900, 2400, and 1600 cm-1 were ascribed to the bands associated with the Brønsted acidic OH groups hydrogen-bonded to DME, and the band at ca. 3300 cm-1 was assigned to the OH stretching m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
4
21
1
Order By: Relevance
“…Higher values of activation energies of desorption of DME than methanol are generally in accordance with previous studies [40,[52][53][54][55] but in contrast to values obtained by Pope [56] through calorimetric methods (Table 5). …”
Section: Comparing Desorption Of Methanol To Dmesupporting
confidence: 92%
“…Higher values of activation energies of desorption of DME than methanol are generally in accordance with previous studies [40,[52][53][54][55] but in contrast to values obtained by Pope [56] through calorimetric methods (Table 5). …”
Section: Comparing Desorption Of Methanol To Dmesupporting
confidence: 92%
“…Feng and Yao suggested that the molecularly adsorbed DME was moderately dissociated on a dehydroxylated ZrO 2 surface, while it rapidly dissociated and no molecularly adsorbed DME could be observed on a fully hydroxylated ZrO 2 surface [43]. Fujino et al suggested that DME molecules adsorbed on OH groups of H-ZSM-5 via hydrogen bonding irrespective of their acidity, and that the oxonium ions of DME were not produced on the studied surface [42].…”
Section: Dme Adsorption Ft-irmentioning
confidence: 99%
“…Further oligomerisation of propylene would then lead to species such as 1-5 hexadiene, which would skeletally rearrange to form cyclic carbocationic species and initiate the aromatic cycle. 16 IR 17,18 and NMR 19 studies show that, even at low coverages, DME can be either physisorbed or chemisorbed to the zeolite, highlighting that there are acid sites in the zeolite catalyst (H-ZSM-5, H-Y) with different bonding capabilities. Theoretical simulations of DME adsorption in zeolite catalysts have been restricted to small cluster models or small unit cell periodic systems (H-ZSM-22), 10,20,21 for which DME adsorption is reported as being feasible in either a physisorbed or a chemisorbed state.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the acid sites of zeolites H-ZSM-5 and H-Y were analysed owing to their different capabilities in adsorbing and activating both methanol and DME, to gain insight into the structural features that can influence catalytic reactivity in zeolites. 11,12,[17][18][19] Our methodology is presented in Section 2, with results presented in the subsequent section.…”
Section: Introductionmentioning
confidence: 99%